Oral vaccine of recombinant Lactococcus lactis expressing the VP1 protein of duck hepatitis A virus type 3 induces mucosal and systemic immune responses. Issue 31 (18th July 2019) - Song, Shasha; Li, Pengfei; Zhang, Ruihua; Chen, Junhao; Lan, Jingjing; Lin, Shaoli; Guo, Guanjie; Xie, Zhijing; Jiang, Shijin
Highlights: A L. lactis expressing VP1 protein of DHAV-3 was successfully constructed. Effective cellular and humoral immunity was induced in the immunized mice. Effective cellular and humoral immunity was induced in the immunized ducklings. The immunized ducklings were effectively protected from natural infection of DHAV-3. Abstract: Duck hepatitis A virus (DHAV) is the major pathogen of duck viral hepatitis, which has caused great economic losses to duck breeding industry. As an effective delivery tool for protein antigens, Lactococcus lactis ( L. lactis ) has been successfully used to stimulate mucosal and systemic immune response. In this study, a recombinant L. lactis named NZ3900-VP1 was constructed, which could express VP1 protein of DHAV type 3 (DHAV-3) by using a nisin-controlled expression (NICE) system. The animal experiment in both mice and ducklings were performed to detect the immune response and protection effect of oral vaccination by the recombinant L. lactis . The results showed that oral vaccination with L. lactis NZ3900-VP1 significantly induced specific anti-VP1 IgG antibodies and mucosal secretory immunoglobulin A (sIgA) of DHAV-3 in mice and ducklings, and cytokines including interleukin-2 (IL-2), interferon gamma (IFN-γ), interleukin-10 (IL-10) and interleukin-4 (IL-4). Notably, the ducklings vaccinated with L. lactis NZ3900-VP1 were effectively protected when facing natural infestation of DHAV-3, which indicated that the recombinant L. lactis could serve as an effective vaccine to prevent DHAV-3 infection in ducklings.